2015
DOI: 10.1038/jhh.2014.131
|View full text |Cite
|
Sign up to set email alerts
|

Cardiocirculatory manifestations in Parkinson's disease patients without orthostatic hypotension

Abstract: The objective of this study was to characterize cardiac sympathetic denervation in Parkinson's disease (PD) patients without neurogenic orthostatic hypotension (NOH), both in terms of hemodynamics and in its relation with vascular denervation. We studied 20 PD patients without NOH. We analyzed the heart rate and blood pressure variability during various physical maneuvers. The following parameters were calculated: expiratory-inspiratory ratio, stroke volume, cardiac output, cardiac index, left ventricular ejec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…Based on previous studies we can presume that this may be an effect of compensatory mechanisms masking loss of direct nervous connection at the cardiac level. 20 Groothuis et al observed that leg vascular resistance increased during 60° head up in PD patients with OH and to a similar extent as in PD without OH and controls, but the small number of subjects and lower tilt angle could explain the difference with our study. 32 All groups showed adaptive changes of cardiovascular parameters in response to orthostatic stress although the profiles of some of these changes were different in the vasodilator group.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Based on previous studies we can presume that this may be an effect of compensatory mechanisms masking loss of direct nervous connection at the cardiac level. 20 Groothuis et al observed that leg vascular resistance increased during 60° head up in PD patients with OH and to a similar extent as in PD without OH and controls, but the small number of subjects and lower tilt angle could explain the difference with our study. 32 All groups showed adaptive changes of cardiovascular parameters in response to orthostatic stress although the profiles of some of these changes were different in the vasodilator group.…”
Section: Discussioncontrasting
confidence: 76%
“…Conversely, Perez et al. found no correlations between the late H/M MIBG ratio and contractility parameters (acceleration index, left ventricular work index, cardiac index, stroke index, left ventricular ejection time) which indicates that cardiac sympathetic denervation by itself is not enough to induce the cardiovascular abnormalities of PD . Interestingly, we also found that the vasodilator PD group had significantly higher resting peripheral vascular resistance values together with significantly lower stroke volume values and cardiac output whereas the sympathetic‐parasympathetic ratio of HRV was not altered.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…denervation in PD patients has been suggested to be more pronounced in the left ventricle (Hakusui et al 1994), which would theoretically limit sympathetic-induced increases in contractility and SVI. However, a study by Perez et al (2015), indicates that in the absence of orthostatic hypotension, the degree of denervation does not produce any effect on inotropic function. Preload, as reflected by EDVI, was lower in PD; therefore, reduced afterload may have allowed for SVI compensation.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study reported that peak heart rate (HR), percentage of age-predicted maximum HR (HR max ) achieved, and peak blood pressure (BP) were significantly lower during a cardiac stress test in individuals later diagnosed with PD compared to those who remained unaffected by the disease (Palma et al 2013). Moreover, Perez et al (2015), provided evidence that sympathetic denervation may affect the heart and the vascular system simultaneously. Researchers have begun to detail the mechanisms and physiological consequences of cardiovascular dysautonomia in PD (Barbic et al 2007, Kim et al 2014; however, few have attempted to identify the presence of cardiovascular abnormalities before, during, and after an exercise stress test.…”
mentioning
confidence: 99%